Role of language discordance in complication and readmission rate after infrainguinal bypass - Inagaki, Elica; Farber, Alik; Kalish, Jeffrey; Siracuse, Jeffrey J.; Zhu, Clara; Rybin, Denis V.; Doros, Gheorghe; Eslami, Mohammad H. (Journal of vascular surgery, 2017)
Studies have shown that language discordance between treatment teams and patients leads to worse patient outcomes, including longer hospital stays, higher rates of readmission, impaired comprehension of discharge instructions, and lower treatment adherence. Yet, there is a paucity of data evaluating the effects of language discordance on postoperative outcomes among vascular surgery patients. This study compared 30-day postoperative complications and readmissions after nonemergent infrainguinal bypass between non-English-speaking (NES) and English-speaking (ES) patients. Consecutive patients who underwent nonemergent infrainguinal bypass for claudication, ischemic rest pain, and tissue loss at an urban, academic medical center between 2007 and 2014 were identified. Patients were stratified into NES or ES groups by their self-identified primary language. Crude comparisons and multivariable analyses were performed to assess the association of primary language status with 30-day wound infections, adverse graft events (wound infections, graft thromboses, or hematomas), readmissions, and Emergency Department return visits. The study included 261 patients who underwent an infrainguinal bypass: 51 NES and 210 ES patients. The NES patients were older (67.4 ± 9.8 vs 63.1 ± 9.9 years; P = .005) and had a higher rate of diabetes (78.4% vs 58.6%; P = .009) and a lower rate of chronic obstructive pulmonary disease (5.9% vs 28.6%; P = .001). Other comorbidities were comparable between the two groups. The NES patients were more likely to be Medicaid beneficiaries (51.0% vs 21.4%; P < .001). Across all outcomes compared, crude analyses showed no significant difference between NES and ES patients. Adjusted analysis revealed that language discordance did not affect the odds of adverse outcomes of wound infections (odds ratio [OR], 1.87; 95% confidence interval [CI], 0.90-3.88; P = .095), adverse graft events (OR, 1.23; 95% CI, 0.62-2.45; P = .556), readmissions (OR, 1.51; 95% CI, 0.77-2.95; P = .478), or Emergency Department return visits (OR, 1.28; 95% CI, 0.58-2.83; P = .546). Our study suggests that language discordance does not affect 30-day complication and readmission rates after infrainguinal bypass.